Obese Children Have a Lower Lipolytic Response to an Acute Bout of Exercise When Compared to Lean - Geyer, Gabriel Hardy (East Carolina University, 2010)
Over 17% of American children are obese. These are epidemic proportions considering the associated risk of heart disease and Type 2 diabetes. Excess fat is caused from an imbalance in energy stored versus energy expended. Previous studies of the fat cell in vitro have revealed differences in the lipolytic response to aerobic exercise in subcutaneous abdominal adipose tissue (SCAAT) from obese and lean adults. There is also evidence that aerobic exercise training can increase SCAAT lipolysis in obese adults. However, review of the literature revealed no studies examining the training response in SCAAT of obese children. The purpose of this study was to determine whether there is a lower lipolytic response to aerobic exercise in SCAAT of obese children. Also, we wanted to know if 16 weeks of aerobic exercise training would increase the lipolytic rates in SCAAT of obese children. In this study, we recruited children from Greenville, NC and surrounding areas. We used the microdialysis technique to examine the lipolytic rate of SCAAT in response to aerobic exercise in forty sedentary children ages 8 to 11. All children and parents were made aware of the risks and benefits of the procedure and signed both consent and assent forms. The study was approved by the East Carolina University International Review Board. Children were grouped by body mass index percentile into obese (n =28) or lean (n =12). Children exercised for twenty minutes at 70% of their heart rate max. In response to exercise, dialysate glycerol concentrations (index of lipolysis) increased in the obese less than the lean (8.1 ± 2.1 uM vs 17.1 ± 4.2 uM, respectively; p <0.05). Changes in SCAAT blood flow, measured by the ethanol outflow; inflow ratio, was not significantly different between the two groups. We also examined the effects of 16 weeks of aerobic exercise training on SCAAT lipolytic response in the obese children (n =21). Children were trained (machines, free play) at an average heart rate of 140 bpm for an hour three times a week. The children returned for another microdialysis session after training. The treadmill speed during the exercise portion after training was the same as that used before training. The change in dialysate glycerol during exercise was not significantly different before and after training (8.9 ± 2.5 and 6.2 ± 2.8 uM respectively; p =0.37). These results suggest that, like adults, obese children have a lower lipolytic response to an acute bout of aerobic exercise than do lean. In addition, 16 weeks of training does not alter lipolytic response to aerobic exercise in obese children when performed at the same absolute intensity before and after training.
Keywords: Health sciences; Obesity in children; Adipose tissues; Aerobic exercises